2019
DOI: 10.1021/acschemneuro.9b00522
|View full text |Cite|
|
Sign up to set email alerts
|

Hybrid Interfaces Made of Nanotubes and Backbone-Altered Dipeptides Tune Neuronal Network Architecture

Abstract: Peptides constituted of backbone homologated -amino acids combined with carbon materials offer interesting possibilities in the modulation of cellular functions. In this work we have prepared diphenylalanine and -peptides and conjugated them to carbon nanotubes (CNTs). These hybrids were capable to self-assemble into fibrillar dendritic structures enabling the growth of primary hippocampal cells and the modulation of their neuronal functions. In particular, following the deposition of the different nanomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In addition, the fibrillar nature of the β- and γ-diphenylalanine peptides in water suggests their use to design novel hydrogels. We have also shown that the β- and γ-diphenylalanine peptides conjugated to carbon nanotubes could self-assemble into fibrillar dendritic structures, favor the growth of neuronal cells, and modulate neuronal functions [ 25 ]. Moreover, we previously reported that l -tyrosine can form well-ordered assemblies with different morphologies, such as nanoribbons, fibers, or branched structures [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the fibrillar nature of the β- and γ-diphenylalanine peptides in water suggests their use to design novel hydrogels. We have also shown that the β- and γ-diphenylalanine peptides conjugated to carbon nanotubes could self-assemble into fibrillar dendritic structures, favor the growth of neuronal cells, and modulate neuronal functions [ 25 ]. Moreover, we previously reported that l -tyrosine can form well-ordered assemblies with different morphologies, such as nanoribbons, fibers, or branched structures [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanomaterials, including CNTs and graphene-family nanomaterials, offer many advantages, not only for neuronal applications [ 25 ], but also as photothermal agents, thanks to their capacity to absorb near-infrared (NIR) light and convert it into heat. Carbon nanotubes (CNTs) are rolled-up graphene sheets of single-layer carbon atoms.…”
Section: Introductionmentioning
confidence: 99%